As ocupações secundaristas e a formação histórica e cidadã de jovens estudantes do ensino médio (Ituiutaba-MG, Brasil, 2016) - Santos, Franciele Amaral Rodrigues dos (2019)
This work proposes to investigate and reflect the experience of young high school students in the secondary occupation of the Governador Israel Pinheiro State School in Ituiutaba, Minas Gerais, Brazil, as a constitutive element of the historical formation and citizen education of secondary school students. It is an opportunity to rethink and reinforce experiences that allow the formation of historical thinking, beyond the classroom. The main objective of the development of this work was to analyze the contributions of the experience of secondary occupations, as a form of struggle, for historical formation and critical education of the young high school students. From this perspective, this work proposes to investigate and reflect on the experience of secondary occupations for the historical formation and citizenship formation of young high school students. It is an opportunity to rethink and reinforce experiences that allow the formation of historical thinking, beyond the classroom. The segment of this work closes theoretical dimensions and interventions in concrete experiences with the secondary students, with the purpose of stimulating the debate on the proposed theme, considering the many questions and the historical context of this event, being recent and dealing with the so - called immediate history. Through interviews we analyze the voices of the students who occupied the school through Oral History and present our perceptions about the results from the interpretation systematized by the theoretical debate presented throughout this work and we identify that the experiences experienced by the young students during the occupation of the State School Governador Israel Pinheiro in Ituiutaba-MG were collaborative for the process of historical and citizen formation when they put themselves in front of articulations and decisions in front of the public policies neglected to the right to a public Education, free and of quality.